PENGARUH EARNING PER SHARE, RETURN ON ASSETS, DEBT TO EQUITY RATIO DAN CURRENT RATIO TERHADAP RETURN SAHAM - Fika Trianti; Dicky Arisudhana (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the partial effects of Earning Per Share (EPS), Return on Assets (ROA), Debt to Equity Ratio (DER), and Current Ratio (CR) on stock returns in Consumer Non-Cyclicals sector, specifically the Food and Beverage subsector listed on the Indonesia Stock Exchange (IDX) during the period 2021– 2024. The research sample was selected using a purposive sampling technique based on specific criteria, resulting in 37 companies being included in the sample. Data analysis was conducted using SPSS version 25 with a multiple linear regression method, focusing on the t-test to examine the influence of each independent variable on stock returns. The results show that partially, EPS has a significant positive effect on stock returns, while ROA has a significant negative effect. In contrast, DER and CR do not have a significant effect on stock returns.